2019
DOI: 10.1111/jcpt.12853
|View full text |Cite
|
Sign up to set email alerts
|

Development and testing of a web module to IMPROVE generic prescribing of oral contraceptives among primary care physicians

Abstract: What is known and objective The use of generic oral contraceptives (OCPs) can improve adherence and reduce healthcare costs, yet scepticism of generic drugs remains a barrier to generic OCP discussion and prescription. An educational web module was developed to reduce generic scepticism related to OCPs, improve knowledge of generic drugs and increase physician willingness to discuss and prescribe generic OCPs. Methods A needs assessment was completed using in‐person focus groups at American College of Physicia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…investigation, but it is beyond the scope of this study. Past studies have suggested that physicians' and nurse practitioners' perception of generics may vary across different types of pharmaceuticals, as do the perceptions of lay people [20,21]. Our study might indicate that manufacturers could take advantage of such perception of inferior quality of generics to maximize their profits at the expense of society at large.…”
Section: Plos Onementioning
confidence: 63%
“…investigation, but it is beyond the scope of this study. Past studies have suggested that physicians' and nurse practitioners' perception of generics may vary across different types of pharmaceuticals, as do the perceptions of lay people [20,21]. Our study might indicate that manufacturers could take advantage of such perception of inferior quality of generics to maximize their profits at the expense of society at large.…”
Section: Plos Onementioning
confidence: 63%